The Effects of Brand Equity, Brand Trust, Product Involvement, Value Consciousness, Attitude and Shariah Compliance on Halal Purchase Intention in Bangladesh: Religiosity as a Moderator - Mohsina Fatema (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis, 2019)
Many researches done on the issue of purchase intention, brands and brand equity but this study focuses only on the Halal paradigm. We have limited our study within the Islamic Banking Industry of Bangladesh. Even though Bangladesh is a Muslim major country, yet awareness and knowledge of what is Halal (allowable in Islam) and what is Haram (forbidden in Islam) is really inadequate (Ullah, 2014). Still majority of the banks are operating in conventional i.e. interest based banking. People follow their religion as some rituals descended from their ancestors, not completely knowing about the actual rules. The brand is a significant interpersonal tool in the service firms' consumer relationship management. Brands are thus valuable to consumers as they minimize the perceived risk of consumption (Aziz & Yasin, 2010). Basic reason for halal branding and positioning is to enter into international business where halal certification has become a prerequisite especially in the Middle East community. Recently, the increase of global sourcing and manufacturing practices have led customers to seek suppliers with an essential level of halal assurance. Since companies tend to scout for consistent methods of standards alongside country borders, Halal certification has been given importance to a greater extent. Many marketers are seeking halal certification, with the hope of an overturn of their poor performance in business in the past, in order to upgrade their business performance. On the other hand, some tend to choose the more conservative goal of retaining customers by agreeing to the needs of their considerable amount of potential customers who are Muslims (Salindal, 2015). In the case of banking, halal assurance is given by shariah compliance. According to Hafij Ullah (2014), the condition of shariah compliance is very vulnerable. This study focuses on the intention of the purchase of shariah compliant Islamic financial products that the Islamic banks are offering. In this regards, customers and prospective customers who bother about consumption of halal products and reside in Bangladesh are selected as the sample of the study.